Multi-color visualization and quantification of single RNA translation and HIV-1 programmed ribosomal frameshifting in living cells - Lyon, Kenneth Ray, Jr., author; Stasevich, Timothy, advisor; Munsky, Brian, committee member; Cohen, Bob, committee member; DeLuca, Jake, committee member (Colorado State University. Libraries, 2019)
Sixty years ago, Francis Crick first stated the central dogma of molecular biology: DNA makes RNA, RNA makes protein. At that time the central dogma could only be imagined, but over the past two decades revolutionary advances in fluorescence microscopy have now made it possible to directly image transcription and translation in living cells and organisms. A key breakthrough was the discovery and development of GFP, which can be genetically fused to other proteins to selectively light them up and track their expression in vivo. While this powerful technology can illuminate mature protein products in live cells, processes like translation remain in the dark. This is because fluorescent fusion tags take too long to mature and light up. By the time the fluorescence becomes visible, translation of a nascent protein is over and has long since separated from its parental RNA strand. This fundamental challenge has made it difficult to visualize, quantify, and study translational gene regulatory mechanisms in living cells and organisms with fluorescence microscopy. To achieve this, nascent chain tracking (NCT) was developed, a technique that uses multi-epitope tags and antibody-based fluorescent probes to visualize and quantify protein synthesis dynamics at the single-RNA level. NCT revealed an elongation rate of ~10 amino acids per second, with initiation occurring stochastically every ~30 seconds. Polysomes contain ~1 ribosome every 200 to 900 nucleotides. By employing a multi-color probe strategy, NCT shows that a small fraction (~5%) form multi-RNA sites in which two distinct RNAs are translated simultaneously while spatially overlapping. NCT was then applied to further understand the dynamics of translating RNAs interactions with ribonucleoprotein (RNP) granules during cellular stress. NCT was used to image real-time single RNAs, their translational output, and RNA-granule interactions during stress. Although translating mRNAs only interact with RNP granules dynamically, non-translating mRNAs can form stable, and sometimes rigid, associations with RNP granules. These stable associations increase with both mRNA length and granule size. Live and fixed-cell imaging demonstrated that mRNAs can extend beyond the protein surface of a stress granule, which may facilitate interactions between RNP granules. Thus, the recruitment of mRNPs to RNP granules involves dynamic, stable and extended interactions affected by translation status, mRNA length and granule size that collectively regulate RNP granule dynamics. Finally, NCT was utilized to quantify the dynamics of multiple open reading frames at the individual RNA level in a living system. An NCT multi-color imaging modality was used to investigate ribosomal frameshifting during translation. Frameshifts occur through a ribosomal +1(-2) or -1 (+2) nucleotide(s) "slip" into another frame and are implicated in both human disease and viral infections. While previous work has uncovered many mechanistic details about single-RNA frameshifting kinetics in vitro, very little is known about how single RNAs frameshift in living systems. Applying multi-frame NCT technology to RNA encoding the -1 programmed ribosomal frameshift (-1PRF) sequence of HIV-1 revealed that a small subset (~8%) of translating RNAs frameshift in living cells. This multi-color NCT method also revealed that frameshifting RNA are preferentially in multi-RNA sites, are translated at about the same rate as non-frameshifting RNA, and can continuously frameshift for more than four rounds of translation. Interestingly, fits to a bursty model of frameshifting constrain frameshifting kinetic rates and demonstrate how ribosomal traffic jams contribute to the persistence of the frameshifting state. These data provide fresh insight into retroviral frameshifting and could lead to alternative strategies to perturb the process in living cells.
Keywords: frameshift; mRNA SG interactions; ribosomal traffic jam; HIV; fluorescence microscopy; nascent chain tracking